Enigma of the Idea from Extending the Village Head Period: Orientation and Implications in a Constitutional Perspective - Hudah, Komsih; Rustan, Ahmad; Irwansyah, Irwansyah (SASI, 2023)
Introduction: In the developing social, political and economic dynamics, the idea of extending the village head's term of office raises questions regarding orientation, legality and its impact in the context of the Indonesian constitution as well as implications for the principles of democracy and community participation in village governance.Purposes of the Research:  This study aims to examine the enigma of the idea of extending the tenure of village heads in the context of village administration in Indonesia and identify the implications of this idea for aspects of democracy, community participation, and the balance of power from a constitutional perspective.Methods of the Research: This study uses a legal analysis and policy analysis approach to examine various laws and regulations related to village governance, including the relevance and implementation of extending the tenure of village heads in Indonesia. The document analysis method will be used to collect data from official sources such as government reports, academic journals, and other trusted publications.Results of the Research: The research results indicate that the enigma of extending the tenure of Village Chiefs in the context of village governance in Indonesia and its relationship with the principles of democracy and community participation as per the Constitution. While the performance of the Village Chief is a consideration, it is important to maintain community participation in the election of Village Chiefs. This extension of tenure has a significant impact on the principle of power rotation, which is essential in safeguarding democracy. Village governance is an integral part of Indonesia's political system, based on democracy and community participation. Although the Village Chief plays a strategic role, the idea of extending their tenure raises important questions related to constitutional principles.